Re: uniting [videorecording (DVD)] - Adkin, Laura; Rand, Krista; Martin, Jesse L.; Harrison, Michelle; Cross, Roger; Moore, Carmen (Gravitas Ventures, 2023)
Follows six best friends from college, now in their 40s, who reconnect for their 25 year reunion weekend. As secrets are revealed, one will force them all to reevaluate their lives.